The association between sugar-sweetened beverages (ssb) consumption, body mass index (BMI) and body fat percentage among undergraduate students in USMKK - Adnan, Anis Suraya (Universiti Sains Malaysia, 2024)
Sugar-sweetened beverages (SSB) consumption led to an increase in BMI and body fat percentage. Furthermore, increase in SSB consumption could also be related to increases in risk of contracting non-communicable disease (NCD). The objective of this study was to determine the association between SSB, BMI and body fat percentage among undergraduate students in USMKK using simple random sampling method. Validated set of self-administered sociodemographic background, pattern of SSB consumption, BEVQ-15, and measurement for BMI and body fat percentage were utilized in this study. Majority of the participants were female (83.1%) and from Malay ethnicity (70.2%). Participants have a normal body weight (58.40%), with ideal body fat for both male (53.5%) and female (60.4%). Overall, the participants had a low SBB consumption (250mL/ day) with sweet tea (with sugar) being the most consumed. While there was a significant association between SSB consumption and BMI, there was no association for SSB consumption and body fat percentage in this study. In conclusion, this study provides insight into the effect of SSB consumption to university students. Thus, it is important to plan an intervention to reduce SSB consumption so we can maintain a normal BMI and body fat percentage, as well as reducing the risk of contracting NCD.